Broadband Circularly Polarized CPW-Fed Monopole Antenna with a Via-Free CRLH-TL Unit Cell - Liangyuan Liu; Xiangqun Shi (International Journal of Antennas and Propagation)
This article presents a broadband circularly polarized composite right/left-hand (CRLH) antenna. A compact microstrip line inductor and an interdigital capacitor are used to form a left-handed parallel inductor and a left-handed series capacitor. The metamaterial parameters of the series inductor and the parallel inductor are optimized. The asymmetric perturbation is introduced to excite the circularly polarized (CP) electromagnetic wave. The influence of interdigital capacitance on the electrical performance of the antenna is analyzed theoretically and experimentally. The value of CL is changed to reduce the electrical size of the antenna, and the resonant frequency of the antenna is reduced accordingly. The physical dimensions of this CPW-Fed monopole antenna are 25 mm∗24 mm∗1 mm. The measured 10 dB wide impedance bandwidth is 79.5%, and the measured 3 dB axial ratio (AR) bandwidth is 56.2%.